2001
DOI: 10.1590/s0037-86822001000200006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da competência vetorial de Lutzomyia intermedia (Lutz & Neiva, 1912) para Leishmania (Viannia) braziliensis, Vianna, 1911

Abstract: This paper investigated the vectorial competence of Lutzomyia intermedia (Diptera: Psychodidae) in Vale do Ribeira (SP) to strains of Leishmania (Viannia) braziliensis (Kinetoplastida: Trypanosomatidae), by means of a search for natural infection; exposure of wild and colonized females (F1) to the lesions of experimentally infected hamsters and transmission tests by bite. The natural infection and the transmission tests were negative. In the exposures of Lu. intermedia to infected lesions we found rates of 74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
4
0
6
Order By: Relevance
“…Experiments have shown that these species may be easily infected with several strains and species of Leishmania (Chagas 1940, Coelho et al 1967, Rangel et al 1992, 1993, Silva & Gomes 2001, which shows that these species are susceptible to infection by Leishmania. In the light of these data, there seems to be little doubt as to the vectorial capacity of N. intermedia and N. neivai.…”
Section: Discussionmentioning
confidence: 97%
“…Experiments have shown that these species may be easily infected with several strains and species of Leishmania (Chagas 1940, Coelho et al 1967, Rangel et al 1992, 1993, Silva & Gomes 2001, which shows that these species are susceptible to infection by Leishmania. In the light of these data, there seems to be little doubt as to the vectorial capacity of N. intermedia and N. neivai.…”
Section: Discussionmentioning
confidence: 97%
“…Silva and Grünewald (1999) Feitosa and Castellón (2004), in the State of Amazonas, found no natural infection in 375 dissected females of 12 sandfly species, the majority of which were Nyssomyia umbratilis. In the State of São Paulo, Silva and Gomes (2001) found no natural infection by the flagellates in 5,448 dissected females, the majority (97.1%) of which were Nyssomyia intermedia, confirming the natural tendency of a low rate of the infection for this species, despite the simultaneous report of high sandfly densities and outbreaks of the ACL. While the dissections carried out on N. intermedia by Silva and Gomes (2001) did not fulfill one of the requirements for the vectorial incrimination (transmission from the vector to a hamster), proposed by Killick-Kendrick and Ward (1981), the experimental infections of this sandfly demonstrated its susceptibility to Le.…”
Section: Resultsmentioning
confidence: 70%
“…Assim, a infecção experimental de flebotomíneos referidos como de L. intermedia, de campo e de laboratório 13 veio contribuir para o esclarecimento desta questão. No entanto, este trabalho, em que foram estudados numerosos insetos do Vale do Ribeira, não faz referência a qualquer dos estudos taxonômicos supracitados, o que deixa o leitor com duas hipóteses, ou seja, que os autores consideram o aspecto taxonômico irrelevante para o seu trabalho ou que não concordam com a distinção entre as espécies.…”
unclassified
“…Se os insetos fossem provenientes de alguma área na qual só tivessem sido encontrados exemplares de uma das espécies do complexo, como o Estado do Rio de Janeiro 9 10 11 , a Argentina 12 ou o interior de São Paulo 2 , seria bastante seguro, com os dados disponíveis, deduzir a qual espécie pertenciam os insetos estudados, mesmo não tendo sido ela devidamente citada. No entanto, por serem os insetos do estudo supracitado 13 de uma área em que ambas as espécies ocorrem 3 4 6 7 8 , só é possível concluir que os insetos pertencem a L. intermedia s. l. Como o trabalho refere-se aos insetos de um estudo do interior de São Paulo 2 como L. intermedia, apesar de todos os exemplares estudados de insetos desta região terem sido identificados como L. neivai 3 4 6 7 8 , permanecem as hipóteses supracitadas sobre as razões dos autores para a não diferenciação.…”
unclassified
See 1 more Smart Citation